Care for a pet bunny - Harkins, Susan Sales; Harkins, William H. (Hockessin, Del. : Mitchell Lane Publishers, 2009)
Presents facts about rabbits as pets, including types and traits, longevity, selection of a healthy, peaceful animal, cage options, toys, feeding, and handling.
Includes bibliographical references (p. 29-30) and index.
3.8
K-3
Keywords: Rabbits -- Juvenile literature; Rabbits; Rabbits